Moje bydgoskie półwiecze. Kapuściska 1957-1959 (Kronika Bydgoska, 2012)
Professor Janusz Rulka, Ph.D., a history teacher from Bydgoszcz, for years connected with the Kazimierz Wielki University o f Bydgoszcz, started his teaching and tutorial career in 1957 at the vocational schools dormitory in Łukaszewicza Street and at the primary school no. 28 in Kapuściska District in Bydgoszcz. He described the experiences from his first job in colourful memoirs.